Hollywood moon : a novel - Wambaugh, Joseph (Little, Brown and Co., 2009)
One moonlit night, LAPD veteran Dana Vaughn and "Hollywood" Nate Weiss, a struggling-actor-turned cop, get a call about a young man who's been attacking women. Meanwhile, two surfer cops known as Flotsam and Jetsam keep bumping into an odd, suspicious duo--a smooth-talking player in dreads and a crazy-eyed, tattooed biker. No one suspects that all three dubious characters might be involved in something bigger, more high-tech, and much more illegal.